Concrete Shear-Friction Material Properties: Application to Shear Capacity of RC Beams of All Sizes. Issue 8 (August 2015) - Chen, Y.; Zhang, T.; Visintin, P.; Oehlers, D.J.
Concrete shear-friction properties are a fundamental material property of concrete which is known to govern not only the shear capacity of reinforced concrete beams and columns but also the flexural ductility that is the ability to rotate and form hinges. In a companion paper, it has been shown how the shear-friction material properties can be extracted from simple confined cylinder tests which will allow these properties to be extracted for a wide range of concrete without undue expense. Also in the companion paper, the shear-friction material properties were derived for normal strength concrete and presented in a generic form suitable for application. In this paper, it will be shown how these generic shear-friction material properties can be used to simulate and quantify the shear-sliding behaviour of initially uncracked concrete generally obtained directly from relatively expensive tests. Furthermore, how these shear-sliding capacities can then be used to quantify the shear capacity of RC beams without stirrups and without the need for size factors as the mechanics based approach automatically, through mechanics, allows for member size.